2003
DOI: 10.1253/circj.67.682
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Performance During Pregnancy in Patients With Repaired Tetralogy of Fallot-Prospective Evaluation Using the Tei Index-

Abstract: Little is known about the influence of hemodynamic changes on ventricular performance during pregnancy in patients with congenital heart disease. A prospective evaluation was made of 17 pregnancies in 11 women with repaired tetralogy of Fallot (ToF). Twenty age-matched non-pregnant women and 41 stable pregnant women without heart disease were studied as controls. Blood pressure (BP), heart rate (HR), left ventricular end-diastolic dimension (LVEDD) and ejection fraction (LVEF), and the Tei index were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
3
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
1
4
3
1
Order By: Relevance
“…In addition, the Tei index closely correlates with patient prognosis, 2-5,13 hemodynamics, [14][15][16] and others. [17][18][19][20][21][22] The present study confirmed these previous findings and further demonstrated the usefulness of the Tei index in the UM-X7.1 hamster model of CHF.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the Tei index closely correlates with patient prognosis, 2-5,13 hemodynamics, [14][15][16] and others. [17][18][19][20][21][22] The present study confirmed these previous findings and further demonstrated the usefulness of the Tei index in the UM-X7.1 hamster model of CHF.…”
Section: Discussionsupporting
confidence: 88%
“…Several reports have described a total of 68 pregnancies in patients with a corrected tetralogy of Fallot. [10][11][12][13][14] No complications were reported in these 68 pregnancies, in contrast to our series.…”
Section: Discussioncontrasting
confidence: 65%
“…Several studies have shown long-term deleterious effects of pregnancy on the heart in women with some cardiac lesions [5][6][7] and late cardiac events have been shown to be more common in women who had a cardiac event in pregnancy. 4 We hypothesised that there would be more cardiac complications in second pregnancies than first, but we found a similar incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Most recent data focus on maternal outcomes during pregnancy, but the impact of the prolonged haemodynamic stress of pregnancy beyond the puerperium is not clear. Late cardiac events in women with heart disease following pregnancy appear to be associated with cardiac events during pregnancy, suggesting that cardiac decompensation during pregnancy in women with heart disease may not be reversible 4 Indeed, data also suggest that pregnancy has an irreversible deleterious effect on ventricular function in women with tetralogy of Fallot 5,6 and a systemic right ventricle. 7 It would seem likely that in women with heart disease, increasing parity might place an additional burden on the already compromised heart, thereby affecting pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%